Analysis of Tourism Cluster Development: Kazakhstan Experience - NIYAZBAYEVA, Aliya; YESSENGELDINA, Anar (Journal of Environmental Management and Tourism, 2016)
At the present moment, formation of clusters in the tourism industry in order to improve the competitiveness of relevant administrative and territorial units has become the most pressing task for Kazakhstan. Formation and development of tourism clusters is the effective mechanism for involvement of foreign direct investments and activation of foreign economic integration. Inclusion of domestic tourism clusters into global value chains will allow raising the level of economic growth essentially by means of raising the international competitiveness of enterprises included into the cluster. The purpose of this article is to analyze the current state of the clustering process in the tourism industry in Kazakhstan and to define the most important causes preventing more complete and effective use of the cluster approach in tourism, as well as to state the recommendations for solution of the problems identified through the means of the state policy. Particular attention is paid to the experience of the Kazakhstan cluster initiative implementation into the tourism industry with the purpose of finding out the key accomplishments and problems of the pilot clusters.
Keywords: tourism; cluster; Kazakhstan; development; cluster initiatives